A rare case of malignant Brenner tumour of ovary: a case report - Jabeen, Syeda Z.; Itagi, Laxmi; Harwal, Neeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ovarian Brenner tumor (BT) is a rare epithelial ovarian cancer that accounts for less than 2% of ovarian neoplasms. The World Health Organization (WHO) classifies Brenner tumors into three categories: benign, borderline and malignant. Malignant Brenner tumors (MBT) of the ovary are 3-5% of Brenner tumors. They carry a poor prognosis. They generally affect women during the perimenopausal and postmenopausal periods and presents with mass per abdomen. A case of 55 years old Female with complaints of post-menopausal bleeding since 3-4 months and pain abdomen since 2 days. Patient attained menopause 20 years ago. Clinically patient appeared stable. On per abdomen hypogastric fullness +, dull note heard over the region. On per speculum examination altered minimal bleeding +, on bimanual examination, mass 10×6 cm in hypogastric region felt separately from fundus of uterus. Serum markers were: beta-human chorionic gonadotropin (b-hCG) – 0.26, alpha-fetoprotein (AFP) – 1.92, CA 125 – 84.18 and anti-Müllerian hormone (AMH) <0.010. Magnetic resonance imaging (MRI) scan showed right ovarian malignant tumour 10.6×14.2×16 cm. Patient was operated and frozen section was sent which confirmed Brenner tumour. Histopathological reporting- malignant Brenner tumour- right ovary. Left ovary and omentum were unremarkable. Ascitic fluid showed malignant cells. Patient was discharged and referred to oncologists. Incidence of malignant Brenner tumour is <2% which makes it uncommon, histopathologically consists of transitional epithelium. We report a case of ovarian malignant Brenner tumour, detailing the clinical presentation, diagnosis, pathologic review, imaging findings, and management.